The preservation and augmentation of volatile terpenes in cannabis inflorescence - Justin Bueno; Emily Leuer; Michael Kearney; Edward H. Green; Eric A. Greenbaum (BMC, 2020)
Abstract Background Terpenes contribute to the pharmacology, efficacy, aroma, and flavor of cannabis inflorescence, improving the experience for medical and recreational users. Terpenes are inherently volatile, resulting in the loss of terpene content as inflorescence ages. A method to establish and/or maintain a desired terpene content of cannabis inflorescence is needed. A novel packaging method was investigated for the preservation of native terpenes and the replenishment of terpenes to depleted inflorescence over various storage durations. Methods Inflorescence samples from two different chemotypes (DJ's Gold, Cream Caramel) were obtained from a state licensed medical cannabis organization. Samples from the DJ's Gold chemotype were depleted of terpenes whereas samples from the Cream Caramel chemotype had a terpene content representative of inflorescence available for medicinal or recreational purposes. Inflorescence samples were stored using the novel packaging approach, in airtight containers in the presence of external terpenes. Control samples were similarly stored without external terpenes. Terpene content of the inflorescence samples were quantitively determined by headspace gas chromatography mass spectrometry (HS GC-MS) after various storage durations. Main effects analysis was used to determine the impact of various parameters on the effectiveness of the system. Results All samples stored using the novel packaging approach had a higher terpene content than their corresponding control. 1.18% (w/w) of external terpene, relative to inflorescence weight, was the minimum amount required to maintain the initial terpene content of the inflorescence after 6 weeks of storage. Main effects analysis showed that augmentation of inflorescence terpene content was dependent upon the amount and type of external volatile utilized. The terpene profile of inflorescence samples from two separate harvests were selectively adjusted, reducing the percent difference of the two sample's terpene profiles by 39.5%. Conclusions A successful proof of concept was achieved for preservation, augmentation, and replenishment of terpenes to cannabis inflorescence over various storage durations. Inflorescence stored using the novel packaging approach is a significant step towards providing patients with cannabis inflorescence of reproducible and reliable terpene content, an important component of inflorescence efficacy. The novel approach for replenishment of terpenes to depleted inflorescence represents an exciting development for patients and manufacturers.